PENGARUH FAKTOR KINERJA KEUANGAN PERUSAHAAN DAN FAKTOR EKONOMI MAKRO TERHADAP KINERJA PASAR SAHAM PADA JAKARTA ISLAMIC INDEX (JII) - Prana, Indra (Aksara Public, 2018)
Investment analysis is very important for investor to make sure that their investment will get return as their expected. Macro economics, industry and company performance are the factors that investor need to observe. The objective of the research was to know the causal relationship of company’s financial performance factors and macro economic factors to Jakarta Islamic Index stock market performance period 2006-2008. This research uses return on equity ratio, current ratio and debt to equity ratio as company’s financial performance factors. Consumer price index or inflation and foreign exchange (USD) used as the macro economic factors. Stocks return used as Stocks market performance indicators. All of these factors and indicator are useful in investment horizon. Multi regression was used to analyze the hypotheses. The result of the research shows that: Company’s financial performance factors and macro economic factors influence stocks return simultaneously. Partially, only debt to equity ratio, inflation and foreign exchange influence the stocks return.